A study on the effectiveness and utilization of courtyard in kulliyyah compound - Ariffin, Norsyahira; Nik Nor Azman, Nik Nor Asiah; Ibrahim, Putri Haryati (2014)
The open spaces are increasing popular in public spaces as well as institutional like schools, colleges, and universities. They can be creating in spaces that are small or large, private or public. Open space can serve many functions in institutional area. The study builds on and contributes to work on the effectiveness and utilization of the courtyard in a campus setting International Islamic University Malaysia (IIUM). It briefly discusses on the functions of courtyard and potential factors that attract the students to utilize the courtyard. The research examines the comparison between the courtyard of the Kulliyyah of Engineering and Kulliyyah of Economic and Management Science as the study area. The analytic focus on the effectiveness of courtyard in the Kulliyyah’s compound enables another contribution. This study also recommends the design criteria and consideration to create successful courtyards at the Kulliyyah’s compound. Questionnaire and observation techniques were used to collect data about students’ awareness, their attitude toward, and their needs towards the courtyard. The preliminary result of the research shows that students with different purposes used courtyard in the Kulliyyah’s. Courtyard in the Kulliyyah’s compound plays important roles toward the users where the courtyard gives positive benefit for the Kulliyyah’s community. The findings concluded that both of the courtyards should be redesign to improve the courtyard area towards a place for education environment and fulfil the users’ needs. Thus, many users can benefit from it. Keywords: courtyard, open space, Kulliyyah, institutional, campus